(Technological) Globalization and Anthropogenic Heritage: Objects and the Distinct Nature of Culture - Kokkinos, Charalampos (Technical Annals, 2023)
The concepts of culture and civilization have been directly linked to the process of social construction since the dawn of human history. A philosophy of civilization presupposes a history of human evolution that would seek to highlight humanity’s achievements through which we have reached the modern age. Now, even more so after the middle of the 20th century, the relationship between material civilization and technology has also been emphasized in the context of the protection of a “global cultural heritage”. Part of this new general concern is the well-known debate about the return of the Parthenon “marbles”. In this article, we will initially focus on the influence of the anthropogenic object heritage on the evolution of societies, arguing that it determines our collective experience and social memory to an important extent. We believe that such an analysis could beneficially contribute to a more meaningful understanding of a crucial topic of our modern technological era, an era that combines the clash of civilizations with globalization. We propose that the vision of a culture as a common possession of all humanity presupposes the respect of each country’s right to possess and care after its own cultural tokens.